2015
DOI: 10.1007/s11745-015-4105-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Omega‐3 Fatty Acids Prevented Adipocyte Hypertrophy by Downregulating DGAT2 and FABP4 in a Sex‐Dependent Fashion

Abstract: Obesity is characterized by an increase in fat mass primarily as a result of adipocyte hypertrophy. Diets enriched in omega (n)-3 polyunsaturated fatty acids (PUFA) are suggested to reduce obesity, however, the mechanisms are not well understood. We investigated the effect of n-3 PUFA on adipocyte hypertrophy and the key genes involved in adipocyte hypertrophy. Female C57BL/6 mice were fed semi-purified diets (20 % w/w fat) containing high n-3 PUFA before mating, during pregnancy, and until weaning. Male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 100 publications
0
13
0
1
Order By: Relevance
“…RNA concentration and purity were measured using NanoDrop 2000 (Thermo Scientific, USA), and cDNA was prepared as per our previous publication . Primers for diacylglycerol acyltransferase‐2 (DGAT2), stearoyl‐CoA desaturase (SCD)‐1, RPLPO (large ribosomal protein) and leptin for quantitative polymerase chain reaction were designed using NCBI primer blast (http://www.ncbi.nlm.nih.gov/ tools/primer‐blast/) as per our previous publication and obtained from IDT technologies (IA, USA). Amplification was performed using iQ SYBER Green Supermix (Biorad, USA).…”
Section: Introductionmentioning
confidence: 99%
“…RNA concentration and purity were measured using NanoDrop 2000 (Thermo Scientific, USA), and cDNA was prepared as per our previous publication . Primers for diacylglycerol acyltransferase‐2 (DGAT2), stearoyl‐CoA desaturase (SCD)‐1, RPLPO (large ribosomal protein) and leptin for quantitative polymerase chain reaction were designed using NCBI primer blast (http://www.ncbi.nlm.nih.gov/ tools/primer‐blast/) as per our previous publication and obtained from IDT technologies (IA, USA). Amplification was performed using iQ SYBER Green Supermix (Biorad, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The final body weight of the db/50% was significantly ( p < 0.05) lower than that of the db/ST, although there were no significant ( p > 0.05) differences in the food intake among the db/ST, db/50%, and db/100% groups (Lee et al, ). The number of laboratory animals used for this experiment was selected based on previous studies (Balogum & Cheema, ; Bargut et al, ; Devarshi et al, ; Fink et al, ; Xu et al, ). All the animal procedures were approved by the Institutional Animal Care and Use Committee of Seoul National University (approval no: SNU‐120630‐4 and SNU‐130617‐2) as reported in the previous articles (Lee et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…The quantity and quality of dietary fat play an important role in the development of obesity (Balogum & Cheema, 2016). Diet with a higher ratio of n-6 to n-3 polyunsaturated fatty acids (PUFA) may increase type 2 diabetes and obesity (Devarshi, Jangale, Ghule, Bodhankar, & Harsulkar, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the CEBPA‐deficient cell, in a sense, can modulate adipocyte differentiation (Liu et al, ; Wang et al, ). Previous studies have indicated that the fatty acid binding protein‐4 (FABP4) has the ability to regulate glucose and lipid metabolism (Balogun & Cheema, ; Xu et al, ). The concerted action of these adipogenic TF ultimately drives the expression of adipocyte‐specific factors, for instance, enzymes that are responsible for the synthesis and storage of triglycerides in lipid droplets (Gregoire, Smas, & Sul, ).…”
Section: Introductionmentioning
confidence: 99%